Possible Association between Methylphenidate and Mandibular Bone Characteristics Detected by Dental Panoramic Radiograph in Children and Adolescents with ADHD - Hadas Kostiner; Lazar Kats; Nurit Kot-Limon; Eran Dolev; Sigalit Blumer (MDPI AG, 2022)
Some studies have shown that children treated with psychostimulants for attention-deficit hyperactivity disorder (ADHD) have decreased bone mineral density (BMD). Mandibular cortical width (MCW) may be used as a surrogate measure for evaluating BMD. We compared the MCW measured on digital panoramic radiographs (DPR) of 38 children and adolescents with ADHD who were treated with methylphenidate for at least 12 months to the MCW of 58 children and adolescents without ADHD (control). The two groups had a similar mean age (p = 0.3). Mean MCW was significantly lower among children with ADHD compared to those in the control group (2.77 ± 0.33 mm vs. 3.04 ± 0.46 mm, p = 0.004). Additionally, each of the MCW sides were significantly smaller in the group with ADHD compared with the control group. In conclusion, treatment with methylphenidate is associated with low MCW in children and adolescents with ADHD. Analysis of MCW on DPR may help in screening children that are at risk of bone health alterations that may result in low BMD in adulthood. Dentists may be the first to identify bone health abnormalities and should be aware of their role in referring their patients to further follow-up.